Efektivitas Chin Tuck Against Resistance (CTAR) pada Disfagia Orofaringeal Paska Stroke: Studi Meta-Analisis - Junaeni Junaeni; Najma Alythea (Politeknik Arutala Johana Hendarto [d.h. Akademi Terapi Wicara], 2023)
This study aims to examine the effectiveness of the chin tuck against resistance (CTAR) approach in reducing aspiration and increasing oral intake in individuals with post-stroke swallowing disorders. This study was a systematic review and meta-analytical design. Electronic database in the form of PubMed is used to search related data. Three experimental articles with a randomized controlled trial (RCT) design were included in this study. Based on related results, it is known that CTAR has an effect on reducing aspiration rate (SMD = -1.03; 95% CI -1.72 – -0.35) and it is known that CTAR has an effect on increasing oral intake (SMD = 0.82; 95% CI 0.03 – 1.61) .